1988
DOI: 10.2337/diab.37.12.1708
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Insulin-Like Growth Factor I Receptors in Diabetes and Other Disorders

Abstract: A newly developed immunoprecipitation assay, with 125I-labeled highly purified human placental insulin-like growth factor I (IGF-I) receptor, was used to search for IGF-I-receptor antibodies in human sera. Eleven of 141 patient sera tested (7.8%) immunoprecipitated labeled IGF-I receptor. Immunoprecipitation was comparable with sera and IgG prepared from these sera. Seven of the 11 sera (3 of 31 with rheumatic disorders, 3 of 48 with non-insulin-dependent diabetes, and 1 of 52 with insulin-dependent diabetes) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our findings may raise a further question about whether myocardial cell death in patients with hypertension induced by Ang II and impaired IGF-I system is caused by an upregulation of IGF-II system and calcineurin activity. In diabetes, IGF-I receptor antibodies bind to the IGF-I receptor at or near the IGF-I binding sites, inhibit IGF-I binding, and probably cause IGF-I resistance [6]. Besides, the circulating IGF-I levels and IGF-I function fall progressively with aging [28].…”
Section: Conclusion and Possible Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings may raise a further question about whether myocardial cell death in patients with hypertension induced by Ang II and impaired IGF-I system is caused by an upregulation of IGF-II system and calcineurin activity. In diabetes, IGF-I receptor antibodies bind to the IGF-I receptor at or near the IGF-I binding sites, inhibit IGF-I binding, and probably cause IGF-I resistance [6]. Besides, the circulating IGF-I levels and IGF-I function fall progressively with aging [28].…”
Section: Conclusion and Possible Clinical Applicationmentioning
confidence: 99%
“…One pathway of angiotensin II induced hypertrophy and apoptosis may be calcium-calcineurin [4]. Besides, patients with diabetes mellitus often exhibit abnormalities in insulin-like growth factor (IGF)-I, such as reduced circulating levels of IGF-I [5] and increased IGF-I resistance [6]. IGF-I has been found to improve myocardial function, promote cardiac growth, improve cardiac contractility, evoke ventricular remodeling, and prevent heart failure [7].…”
Section: Introductionmentioning
confidence: 99%
“…(19) re~orted that sera from five of seven ~atients with severe ins;linmresistance and acanthosis nigricans i&unoprecip-itated both placental insulin and IGF-I receptors. Autoantibodies to the IGF-I receptor were also found in &ra from 1 1 patients with a variety of disorders reported to have an increased prevalence of insulin receptor antibodies (7). In this study, two sera from patients with severe insulin resistance type B were found to immunoprecipitate the labeled IGF-I receptor and to inhibit IGF-I binding.…”
Section: Resultsmentioning
confidence: 69%
“…Patients with diabetes often show reduced circulating levels of IGF-I and thus develop IGF-I resistance [ 7 , 8 ]. This situation may induce apoptosis of myocardial cells and increase the risk of a heart attack.…”
Section: Introductionmentioning
confidence: 99%